How to do the work : recognize your patterns, heal from your past, and create your self - LePera, Nicole (New York, NY : Harper Wave, 2021)
"From Dr. Nicole LePera, creator of "the holistic psychologist"-the online phenomenon with more than 2M followers on Instagram-comes a revolutionary approach to self-improvement, integrating the tools of various modalities and disciplines with traditional psychology to offer a practical program that guides readers to create radical change"--
Preface: Dark night of the soul -- Introduction: Primer on holistic psychology -- You are your own best healer -- The conscious self : becoming aware -- A new theory of trauma -- Trauma body -- Mind-body healing practices -- The power of belief -- Meet your inner child -- Ego stories -- Trauma bonds -- Boundaries -- Reparenting -- Emotional maturity -- Interdependence -- Epilogue: The pizza box.
Includes bibliographical references and index.
HB
Keywords: Mind and body; Healing -- Psychological aspects; Self-help techniques